2010
DOI: 10.1103/physrevd.82.043521
|View full text |Cite
|
Sign up to set email alerts
|

Bimetric structure formation: Non-Gaussian predictions

Abstract: The minimal bimetric theory employing a disformal transformation between matter and gravity metrics is known to produce exactly scale-invariant fluctuations. It has a purely equilateral non-Gaussian signal, with an amplitude smaller than that of DBI inflation (with opposite sign) but larger than standard inflation. We consider non-minimal bimetric models, where the coupling B appearing in the disformal transformationĝ µν = g µν − B∂ µ φ∂ ν φ can run with φ. For power-law B(φ) these models predict tilted spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 65 publications
1
65
0
Order By: Relevance
“…In a recent paper [15] it was shown that the cuscuton-like model also leaves a potentially observable non-Gaussian signature in the CMB anisotropy field, f NL ∼ O(1), which is slightly different from the signatures of other superluminal models discussed in the literature [16,17]. This difference is due to the contribution of the termζ 3 in the cubic action [18,19] to the full non-Gaussian amplitude, giving rise to an extra term with a linear dependence on the flow parameters and s. This dependence is not present either in DBI models (since the coefficient ofζ 3 in the third-order action is identically null in this case), or in disformal bimetric model [16], since by projecting its scalar-field action in the Einstein frame one obtains a DBI-like action. Therefore, the cuscuton tachyacoustic model "inherits" an extra contribution from theζ 3 term, providing a different value for f NL compared to the other superluminal models.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent paper [15] it was shown that the cuscuton-like model also leaves a potentially observable non-Gaussian signature in the CMB anisotropy field, f NL ∼ O(1), which is slightly different from the signatures of other superluminal models discussed in the literature [16,17]. This difference is due to the contribution of the termζ 3 in the cubic action [18,19] to the full non-Gaussian amplitude, giving rise to an extra term with a linear dependence on the flow parameters and s. This dependence is not present either in DBI models (since the coefficient ofζ 3 in the third-order action is identically null in this case), or in disformal bimetric model [16], since by projecting its scalar-field action in the Einstein frame one obtains a DBI-like action. Therefore, the cuscuton tachyacoustic model "inherits" an extra contribution from theζ 3 term, providing a different value for f NL compared to the other superluminal models.…”
Section: Introductionmentioning
confidence: 90%
“…(16). The resulting model is tachyacoustic, that is, has a decaying, superluminal speed of sound and shrinking acoustic horizon in comoving units.…”
Section: Attractor Behavior a The Cuscuton Casementioning
confidence: 99%
“…The trick was used in [21,22] to derive the cubic action for theories with a varying speed of sound [2,3] and their non-Gaussianities.…”
Section: Rainbow Gravity and Linearizing Variablesmentioning
confidence: 99%
“…Bimetric varying speed of light theories [27] and tachyacoustic cosmology [28] are two possible ways of putting this mechanism to work. The minimal bimetric theory leads to scale-invariant perturbations but it is also possible to obtain deviations from strict scale-invariance, subject to consistency relations involving the 3-point function [29,30]. It is also possible to implement this mechanism via deformed dispersion relations [31], as we now review.…”
Section: Cosmological Perturbationsmentioning
confidence: 99%